A numerical approach for acoustic radiation and scattering of moving bubbles at low frequencies - Li, Yi-Fan; Zhang, Yong-Ou; Qu, Yao; Zhang, Tao (Frontiers in Physics, 2023)
The acoustic radiation and scattering of underwater bubbles plays an important role in ocean exploration, target localization, acoustic measurements, etc. The two-phase fluid flow and moving boundary result in the lack of means to predict the sound field, which limits the exploration of relevant characteristics and mechanisms. The present work is intended to introduce a numerical approach for acoustic radiation and scattering of moving bubbles at low frequencies with CFD-BEM coupling method. The two-phase interface is captured with the volume of fluid scheme and the sound field is solved with the BEM. After that, some benchmark problems are solved and the results are compared with data from literatures. Finally, the radiation and scattering of moving bubbles at low frequencies are predicted with our approach. The radiated sound pressure of the bubble increases gradually during the deformation process. With the increase of ka value, a main lobe and side lobe appears, and the energy of the acoustic scattering is gradually concentrated in the forward direction of the incident wave. For a 10 mm bubble moving in a straight line, a distance of about 1m can deflect the far-field acoustic directivity by 1°.